Evaluasi Kepuasan Pasien Rawat Jalan terhadap Kualitas Pelayanan di Instalasi Farmasi Rumah Sakit X di Kabupaten Klaten: Evaluation of Outpatient Satisfaction with Service Quality at the Pharmacy Department of Hospital X in Klaten Regency - Imam Sahid Cahyono; Isna Nur Khasanah; Tatiana Siska Wardani (Jurnal Ilmiah Farmasi Indonesia (JIFIN), 2023)
Patient satisfaction is an assessment of a patient between service performance or perceived and expected satisfaction. Patient satisfaction will be fulfilled if the services provided are in accordance with patient expectations. Assessment of satisfaction is not only limited to physical recovery, but also from communication, physical facilities, friendliness of staff, responsiveness of officers in serving patients. This study aims to evaluate outpatient patient satisfaction with the quality of pharmacy services at the X Hospital, Klaten Regency. This research was conducted using the Service Quality (SERQUAL) method which has five dimensions, namely tangible, reliability, responsiveness, assurance and empathy. The results of this study are questionnaire data from 380 respondents getting results from the five dimensions of service quality consisting of 25 questions having a positive gap value. The highest gap value is 0.13 on the responsiveness dimension and the lowest gap value is 0.04 on the tangible dimension. Based on the results of this study, it can be concluded that the services provided by the X Klaten hospital to patients can be said to be good, and the results of these measurements can be used as an evaluation in improving the quality of hospital.